Translation und Exil (1933-1945) I Namen und Orte. Recherchen zur Geschichte des Übersetzens - Tashinskiy, Aleksey; Boguna, Julija; Rozmysłowicz, Tomasz (Frank & Timme, 2022)
Research into exile has so far focused on numerous groups of people persecuted by the National Socialists: Writers, artists, scientists, politicians and many others. One group, however, has remained largely invisible until now: translators. How did they get to their places of exile? What did they translate there, how and why? The authors of this book pursue these questions in material-rich studies and show the complex connection between translating and the experience of exile. In doing so, they open up an exciting new area for historical exile research, in which most of what seemed to have been said already.